PENERAPAN K-MEDOID PADA RUMAH TANGGA YANG MEMILIKI SUMBER PENERANGAN LISTRIK PLN BERDASARKAN PROVINSI - Cici Astria; Agus Perdana Windarto; Dedy Hartama (STMIK Budi Darma, 2019)
Electricity has now become something that is very much needed in daily life, every household has used PLN electricity lighting sources. However, there are also some regions in Indonesia that have not been able to enjoy good and even electric lighting. The data source used from the Indonesian Statistics Agency website is the Percentage of Household Data by Province and Treatment, 2013-2014. This study aims to classify households that have a source of electricity for PLN using the datamining algorithm with K-Medoid. The data is processed into 2 clusters, namely high level clusters (C1) and low level clusters (C2). Where the results of this study concluded from 33 provinces in Indonesia that the cluster level of low waste sorting behavior (C1) obtained 11 provinces namely Aceh, Kep. Bangka Belitung, DKI Jakarta, West Java, Central Java, DI Yogyakarta, East Java, Banten, Bali, West Nusa Tenggara, and North Sulawesi and 23 other provinces are included in the low-level cluster (C2).Keywords: Electricity, Datamining, K-Medoid, Clustering, Household Sources